(untitled) (Olhares, 2025)
This article deals with the documentary film Todas por uma (2022), by Jeanne Dosse, which shows how, in the midst of the economic, political, social and cultural crises that devastated Brazil, Ariane Mnouchkine, director of the Théâtre du Soleil (France), was invited to supervise the staging of the play As comadres (2019), a version of Les Belles-Soeurs (1965) by the Canadian Michel Tremblay, turned into a musical in 2010, by René Richard Cyr, with more than twenty Brazilian actresses, in an approach collaborative that aimed to break with the dominant patterns and give rise to a collective work. In addition to highlighting the encounter between Mnouchkine and Brazilian theater, the article also seeks to point out the clues that show the strong connection between Ariane and the cinema, explicit in the way in which the director and filmmaker conducts her creation processes and invents languages through images.